El impacto de la estructura productiva en la globalización económica: un enfoque cuantitativo a nivel mundial en el periodo 1995-2019. - Valle Vásquez, Tonny Brayan (2023)
Economic globalization over time has played an important role in the exchange of products at the international level, since in the year 2021 at the global level it showed that agriculture represents negative values of 1.48%, which is of concern for developing countries. In this context, the aim is to evaluate the impact of the productive structure on economic globalization, taking into consideration a worldwide approach, using econometric methods in order to propose policy techniques aimed at value-added commercialization. For which, statistical information from the database of the World Bank (2021), Swiss Economic Institute KOF (2021) was used. In addition, in order to meet this research objective, three tests were applied: generalized least squares (GLS), cross-sectional CS-ARDL model and, causality test of Dimitrescu and Hurlin (2012). The results obtained with both short and long term estimates show that in the short term industry has a negative relationship at the global level and in the long term agriculture and industry have a positive relationship at the global level. The policy implications should focus on generating greater investment in the most vulnerable economic sectors of the least developed countries, since these countries should take into account that changing trade policies can have a more positive effect on their economies.